A comparative study of power sources for base transceiver station - Mahbub, Md. Pavel; Abedin, Syed Minhajul; Arman, Sarwar Ali; Rahman, Md. Mahmudur (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.